Effects of dietary supplementation of alfalfa meal on growth performance, carcass characteristics, meat and egg quality, and intestinal microbiota in Beijing-you chicken. (29th November 2018) - Zheng, Mingli; Mao, Peichun; Tian, Xiaoxia; Guo, Qiang; Meng, Lin
ABSTRACT: This study was conducted to investigate the effects of alfalfa meal supplementation on growth performance, carcass characteristics, meat and egg quality, and intestinal microbiota in chickens. A total of 600 healthy 20-wk female Beijing-you chickens (a local Chinese chicken breed) were selected and randomly assigned into 4 dietary treatments: 0, 5, 8, and 10% alfalfa meal supplementation. Chickens were raised in a free-range system for 56 d. Microbiota inhabiting 3 different intestinal sections (duodenum, ileum, and cecum) was determined using high-throughput sequencing. The results showed that chickens given alfalfa meal had lower ( P < 0.05) feed conversion ratio, mortality, abdominal fat yield, and yolk cholesterol content, and higher ( P < 0.05) breast muscle contents of inosine monophosphate, total amino acids, essential amino acids, non-essential amino acids, delicious amino acids, yolk protein, albumen protein, and yolk color compared to those given no alfalfa meal. The Lactobacillus was the dominant genus in both duodenum and ileum, while the microbiota in cecum was mainly composed of the Bacteroides . Although small changes in the dominant intestinal microbiota of chickens fed with or without alfalfa meal were observed, supplementation of alfalfa meal tended to stimulate the proliferation of beneficial bacteria, such as the Lactobacillus and Bacteroides, and inhibit potential pathogens, including the Clostridium . Therefore, dietary supplementation of alfalfa meal was feasible to Beijing-you chickens raised in a free-range system, and 10% was recommended as the relatively optimal level.